Correction to: Systematic review of the relationships between physical activity and health indicators in the early years (0-4 years) - Valerie Carson; Eun-Young Lee; Lyndel Hewitt; Cally Jennings; Stephen Hunter; Nicholas Kuzik; Jodie A. Stearns; Stephanie Powley Unrau; Veronica J. Poitras; Casey Gray; Kristi B. Adamo; Ian Janssen; et al. (BMC, 2017)
Correction After publication of the article [1], it has been brought to our attention that an incorrect reference has been used in this article, both in the main body and additional file 2. The reference in question is #105 in the main body and #74 in additional file 2. Here it is cited as "Lindsay H, Brussoni M. Injuries and helmet use related to non-motorized wheeled activities among pediatric patients. Chronic Dis Inj Canada. 2014;34(2-3):74-81".